Chiroptical Properties and the Racemization of Pyrene and Tetrathiafulvalene-Substituted Allene: Substitution and Solvent Effects on Racemization in Tetrathiafulvalenylallene - Masashi Hasegawa; Seiya Iwata; Yasuto Sone; Junta Endo; Hideyo Matsuzawa; Yasuhiro Mazaki (Molecules, 2014)
Dissymmetric 1,3-diphenylallene derivative 3 connected with 4,5-bis(methyl-thio)tetrathiafulvalenyl and 1-pyrenyl substituents was prepared and characterized. The molecular structure was determined by X-ray crystallographic analysis. Optical resolution was accomplished using a recycling chiral HPLC, and its chiroptical properties were examined with optical rotation and electronic circular dichroism (ECD) spectra. The title compound underwent photoracemization under daylight. This behavior was investigated in various solvents and compared with that of 1,3-bis(tetrathiafulvalenyl)allene (bis-TTF-allene) derivative 2. The first-order rate plot of the intensity of the ECD spectra at a given time interval gave the rate of racemization. Mild racemization was observed in polar solvents, whereas a relatively fast rate was obtained in less polar solvents. In addition, the TTF groups of the allene also accelerate the racemization rate. These results suggest that the racemization mechanism occurs via a non-polar diradical structure.